2018
DOI: 10.13005/bpj/1449
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Microrna Expression within the Cells of Peripheral Blood Mononuclear after an Infection with Serotype-2 of Dengue Virus: Preliminary Study

Abstract: The role of microRiboNucleic Acids (miRNA), a small-non coding RNA has been associated with immune regulation in various viral infectionincluding dengue infection. The microRNA will bind a specific protein target in order to encourage an explosive expression of various cytokines, known as cytokines storm in Dengue infection.The objective of this study aimed to determine and evaluate themicroRNAs profile expression withinperipheral blood mononuclear cells having been infected with one of the dengue virus seroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…miR-146a, miR-150, let-7e was reported to be induced upon DENV infection suggesting their role in dengue pathogenesis. 43 miR-146a was found to facilitate DENV replication in the human monocytes and macrophage cell line. 35 However, another study identified no effect of miR-146a overexpression of DENV replication in human lung cell-line, A549, possibly due to a cell-type specific effect of miRNAs.…”
Section: Mirnas Targeting Viral Genome To Develop Antiviral Statementioning
confidence: 98%
See 2 more Smart Citations
“…miR-146a, miR-150, let-7e was reported to be induced upon DENV infection suggesting their role in dengue pathogenesis. 43 miR-146a was found to facilitate DENV replication in the human monocytes and macrophage cell line. 35 However, another study identified no effect of miR-146a overexpression of DENV replication in human lung cell-line, A549, possibly due to a cell-type specific effect of miRNAs.…”
Section: Mirnas Targeting Viral Genome To Develop Antiviral Statementioning
confidence: 98%
“…35 However, another study identified no effect of miR-146a overexpression of DENV replication in human lung cell-line, A549, possibly due to a cell-type specific effect of miRNAs. 44 Similarly, induction of hsa-let-7c, hsa-miR-146a differs in DENV infection ex-vivo in PBMCs [41][42][43] compared to DENV2 infection in human macrophage cell lines. 35,39 DENV infection progression is systematic and dynamic under the infection.…”
Section: Mirnas Targeting Viral Genome To Develop Antiviral Statementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, miR-30e also expresses differentially in dengue infected cultured cells [24]. miR-150 expression is upregulated in DENV infected cultured cells within few hours of the infection [25]. Expression of miR-150 is also found to be significantly upregulated in SD patients compared to DF patients [26].…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, miR-30e-3p also express differentially in dengue infected cultured cells [24]. miR-150 expression is upregulated in DENV infected cultured cells within few hours of the infection [25]. Expression of miR150 is also found to be significantly upregulated in DHF patients compared to DF patients [26].…”
Section: Introductionmentioning
confidence: 99%